2022
DOI: 10.3390/jof8070674
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole for COVID-19-Associated Invasive Mold Infections

Abstract: Isavuconazole is a broad-spectrum antifungal drug recently approved as a first-line treatment for invasive aspergillosis and as a first or alternative treatment for mucormycosis. The purpose of this review was to report and discuss the use of isavuconazole for the treatment of COVID-19-associated aspergillosis (CAPA), and COVID-19-associated mucormycosis (CAM). Among all studies which reported treatment of CAPA, approximately 10% of patients were reportedly treated with isavuconazole. Considering 14 identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…In addition, the authors emphasized the negative impact of plasma on the antifungal activity, which may overestimate the efficacy found in vitro for isavuconazole in this study, as similar results were found in studies on posaconazole [ 46 ]. Furthermore, isavuconazole appears to have significant inter-individual variability [ 23 , 47 ]. Microbiologically, the EUCAST threshold in 01/2022 was set at 2 mg/L for isavuconazole [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors emphasized the negative impact of plasma on the antifungal activity, which may overestimate the efficacy found in vitro for isavuconazole in this study, as similar results were found in studies on posaconazole [ 46 ]. Furthermore, isavuconazole appears to have significant inter-individual variability [ 23 , 47 ]. Microbiologically, the EUCAST threshold in 01/2022 was set at 2 mg/L for isavuconazole [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases the volume of distribution, 20,21 and it was shown that the clearance of other related azole antifungals like voriconazole is higher 22,23 . It was previously concluded that the BMI might influence the exposure to isavuconazole, suggesting that patients with severe obesity might have lower therapeutic drug levels 13 . Another possible reason for lower C min levels in critically ill patients could be an increased volume of distribution in the early phase of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…CARDS‐patients commonly suffer from fungal superinfections, 10–12 such as COVID‐19‐associated pulmonary aspergillosis (CAPA) and COVID‐19‐associated mucormycosis (CAM). Such patients are frequently obese and hospitalised with concomitant renal replacement therapy (RRT) or extracorporeal membrane oxygenation (ECMO) requirement which can affect isavuconazole levels 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, Troutine monitoring of isavuconazole levels was not considered, based on data from a pivotal study that found no association between blood levels and drug efficacy and/or toxicity. An analysis of eight studies in which isavuconazole levels were monitored in a total of 368 patients produced no conclusive findings in this regard [ 38 ]. However, suboptimal isavuconazole concentrations have been reported in critically ill patients, and are more frequent in obese patients and those undergoing renal replacement techniques [ 19 ].…”
Section: Question 6: In What Situations Should We Monitor Whether Tre...mentioning
confidence: 99%